2011
DOI: 10.1002/nme.3200
|View full text |Cite
|
Sign up to set email alerts
|

An augmented cohesive zone element for arbitrary crack coalescence and bifurcation in heterogeneous materials

Abstract: SUMMARYWe demonstrate that traditional cohesive zone (CZ) elements cannot be accurate when used in conjunction with solid elements with arbitrary intra-element cracking capability, because they cannot capture the load transfer between cohesive interfaces and the solid elements when crack bifurcation or coalescence occurs. An augmented cohesive zone (ACZ) element based on the augmented finite element method formulation is therefore proposed. The new element allows for arbitrary separation of the cohesive elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 50 publications
2
47
0
Order By: Relevance
“…However, Fang et al [33] indicated that traditional cohesive elements used in conjunction with XFEM modeling intra-element cracking could not capture the load transfer between the interface elements and solid elements when crack bifurcation or coalescence occurs in heterogeneous materials. This phenomenon was also observed in debonding analyses that simulate the fiber/ matrix interface using a thin cohesive layer made up of cohesive elements, as shown in Fig.…”
Section: Czm For Fiber/matrix Debondingmentioning
confidence: 99%
“…However, Fang et al [33] indicated that traditional cohesive elements used in conjunction with XFEM modeling intra-element cracking could not capture the load transfer between the interface elements and solid elements when crack bifurcation or coalescence occurs in heterogeneous materials. This phenomenon was also observed in debonding analyses that simulate the fiber/ matrix interface using a thin cohesive layer made up of cohesive elements, as shown in Fig.…”
Section: Czm For Fiber/matrix Debondingmentioning
confidence: 99%
“…In the heterogeneity of an advanced composite, failure occurs by a complex combination of interacting cracks and local damage events, which are governed by nonlinear material behavior. Key advances in theory have enabled a realistic depiction of the nonlinear mechanics of crack initiation, growth, bifurcation, and coalescence; critically, the location and path of each crack are determined by local stress conditions during a simulation, rather than being prescribed in advance (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Fidelity in simulations was impossible before such generality was achieved.…”
Section: The Purpose Nature and Challenges Of Virtual Testsmentioning
confidence: 99%
“…Consider the case of Figure 19, which shows simulations of transverse cracks formed by the coalescence of interfacial and matrix microcracks (23). The fiber-scale simulations analyze virtual specimens of random fiber arrays, with distinct cohesive fracture laws operating at fiber/matrix interfaces and within the matrix.…”
Section: Fiber-scale Simulations Predict Tow-scale Fracture Lawsmentioning
confidence: 99%
“…The original version of the A-FEM and the RxFEM have been successfully used to study multiple arbitrary cracking problems in laminated composites [21,[26][27][28]. In these studies, the coupling between intra-ply cracks and delaminations were done through proper designation of different types of elements for different failure processes, i.e.…”
Section: Introductionmentioning
confidence: 99%